ANALYSIS THE ROLE OF INSTAGRAM AND TELEVISION IN ATTRACTING PUBLIC INTEREST IN THE SHOPEE APPLICATION - Varid Martah; Fitri Nurhidayati (Utiliti Project Solution, 2026)
Previous studies have often examined the role of social media or television advertisements separately in e-commerce marketing, yet few have conducted a comparative and integrative analysis of both, particularly in Indonesia's peri-urban areas. This study aims to analyze and compare the roles of Instagram social media and television advertisements in attracting public interest to download the Shopee application, with a case study in Kelurahan Karang Pilang as a location representing the transition of an urban community with access to both media. A qualitative research method was employed through in-depth interviews with seven purposively selected informants. The findings reveal that Instagram plays a significant role through creative ad content, high posting frequency, and active user engagement, particularly among the younger demographic. Meanwhile, television advertisements are effective in reaching a broader and more age-diverse audience, primarily through the power of audio-visual elements and high airing frequency, showing greater influence on older age segments. This study highlights the need for an Integrated Marketing Communications (IMC) strategy that considers media characteristics and audience segmentation. As a practical implication, Shopee is advised to optimize Instagram content with personalized promotions for young users while maintaining the production quality and reach of television ads for the mass audience. For future research, it is recommended to expand the sample size and employ a mixed-methods approach for broader generalizability.